Perancangan Simulasi Antena Mikrostrip Dengan Slot Butterfly Untuk Aplikasi WiFi Pada Frekuensi Kerja 5,8 GHz Menggunakan CST Microwave Studio - Meliza Sukma Riani; Yusnita Rahayu (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2016)
Wi-Fi is a technology that is very poluler today. WiFi is an abbreviation of Wireless Fidelity, is a set of standards used for Wireless Local Network (LAN Local Area Networks) whose function is to connect local area networks in a wireless manner. Along with the evolution of telecommunications technology based on wireless technology, then we need for a communication system that can perform high-speed data transmission with good quality. One of the devices supporting wireless communication devices is the antenna. The use and selection of antennas is one of the important factors that affect the performance of the antenna as well as good design and proper installation will ensure the performance of the telecommunications system. Microstrip antenna has the advantages of low profile form, which is easy and inexpensive to produce in mass but has a small gain and bandwidth. This paper discusses the design of the Microstrip antennas patch for WiFi applications that operate at a frequency of 5.8 GHz . In this design uses FR4 epoxy material = 4.4 and a thickness of 1.6 mm, is suitable for application of high-frequency antenna. For the simulation in this paper using the software CST Microwave Studio. From the results of the design using CST studio microvawe is obtained in accordance with the specification antenna, with VSWR ≤ 1.5, gain ≥ 2 dB and return loss ≥ 20 dB.Keywords: Microstrip Antenna,, WiFi, Gain, VSWR, Return Loss